THE IMPLEMENTATION OF IMPROMPTU SPEECH METHOD IN TEACHING SPEAKING HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS AT SMAN 1 KRIAN (RETAIN, 2014)
THE IMPLEMENTATION OF IMPROMPTU SPEECH METHOD IN TEACHING SPEAKING HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS AT SMAN 1 KRIAN Mega Sari Trismianti English Department, Languages and Arts Faculty, State University of Surabaya cutezmega63@yahoo.co.id Esti Kurniasih, S.Pd., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya estikurniasih87@yahoo.com Abstrak Banyak siswa yang enggan berbicara bahasa Inggris di dalam kelas. Hal ini merupakan masalah serius yang sedang dihadapi oleh guru bahasa Inggris saat ini. Bahasa Inggris adalah bahasa komunikasi, itu berarti dalam mempelajari bahasa Inggris siswa harus dapat berbicara Inggris dengan lancar. Untuk menyelesaikan masalah ini, guru seharusnya mengetahui karakteristik siswa. Siswa kelas sebelas merupakan siswa yang berada pada tingkat intermediate menuju ke tingkat advanced. Siswa dalam tingkatan ini membutuhkan kesempatan untuk mengekspresikan diri mereka. Mereka membutuhkan metode penyampaian berbicara bahasa Inggris yang menantang, seperti berpidato mendadak. Sementara itu, terdapat beberapa teks yang harus dipelajari oleh siswa di semester genap, teks hortatory exposition adalah teks yang dipilih untuk penelitian ini karena teks tersebut cocok untuk berpidato secara mendadak. Dilakukannya penelitian ini dengan tujuan untuk mendeskripsikan pelaksanaan berpidato mendadak dalam pengajaran berbicara teks hortatory exposition untuk kelas sebelas di SMAN 1 Krian, respon siswa terhadap pelaksanaan berpidato mendadak dalam pengajaran berbicara teks hortatory exposition, penampilan siswa saat berbicara dengan menggunakan teks hortatory exposition selama pelaksanaan berpidato mendadak dalam pengajaran berbicara teks hortatory exposition. Karena penelitian ini mendeskripsikan peristiwa-peristiwa yang dilakukan oleh siswa dan guru secara alami, maka metode yang digunakan dalam penelitian ini adalah deskriptif qualitatif. Lembar cacatan, angket terstruktur, dan hasil penampilan siswa dalam berbicara teks hortatory exposition adalah alat yang digunakan dalam memperoleh data untuk penelitian ini. Berdasarkan data yang diperoleh, hasil menunjukkan bahwa berpidato mendadak berhasil digunakan dalam pengajaran berbicara teks hortatory exposition untuk kelas sebelas di SMAN 1 Krian. Sementara itu, hasil juga menunjukkan bahwa siswa tertarik dalam mempelajari teks hortatory exposition dengan menggunakan metode penyampaian pidato secara mendadak. Hasil akhir menunjukkan bahwa pelaksanaan metode berpidato mendadak dapat membantu siswa kelas sebelas di SMAN 1 Krian dalam mempelajari berbicara teks hortatory exposition. Kata kunci: berbicara, metode berpidato mendadak, teks hortatory exposition, siswa kelas sebelas, respon siswa Abstract Many students are reluctant to speak English in the class. It is a serious problem which is being faced by English teacher nowadays. Because English is a language, it means that in learning English, the students must be able to speak English fluently. To solve this problem, the teacher should know the students’s cheracteristics. The eleventh graders are supposed to be intermediate to advanced level. Students in this level need opportunites to express themselves. They need a challenging method in delivering their speaking, such as impromptu speech. Meanwhile, there are several texts that must be learned by the students in the even semester. Hortatory exposition text was the chosen text because it matches to the impromptu speech method. This study aimed to describe the implementation of impromptu speech method in teaching speaking hortatory exposition text to the eleventh graders of SMAN 1 Krian, the students’ responses toward the implementation of impromptu speech method in teaching speaking hortatory exposition text, and the students’ hortatory exposition speaking performance during the implementation of impromptu speech method in teaching speaking hortatory exposition text. Due to describing the phenomena of the human participants in natural settings, descriptive qualitative was used in this study. Field notes, structured questionnaire, and students’ hortatory exposition speaking performance results were applied as research instruments to obtain the data. Based on the collected data, the results showed that the impromptu speech method was successfully used to teach speaking hortatory exposition text to the eleventh graders of SMAN 1 Krian. Meanwhile, the students were also interested in learning speaking hortatory exposition text by using impromptu speech method. Finally, the use of impromptu speech method could help the eleventh graders in learning speaking hortatory exposition text. Keywords: speaking, Impromptu Speech Method, Hortatory Exposition text, eleventh graders, students’ responses INTRODUCTION Speaking is one of the productive skills in English. Therefore, teaching speaking is more difficult than teaching listening and reading, because the teacher must encourage the students to produce language orally. Mostly, many students do not like when the teacher asks them to speak in front of the class. It is caused by many factors: they are afraid of making mistakes, the topic are not interesting, the classroom atmosphere is not encouraging, and the feedback from listeners is not supportive (Jianing, 2007) Considering the factors above, the teacher must not teach speaking monotonously. She has to know the students’ characteristics in order the students can enjoy learning and teaching process. In high school cognitive development, the students need to understand the purpose and relevance of instructional activities; they are also both internally and externally motivated. Meanwhile, in high school development, the students develop a community consciousness and need opportunities for self-expression(Pennington, 2009). Based on the students’ characteristics above, the teacher must choose a creative technique in teaching speaking. However, the teacher should consider first the types of classroom speaking performance, such as imitative, intensive, responsive, transactional (dialogue), interpersonal (dialogue), and extensive (monologue). In this study, the researcher tends to use monologue in classroom speaking performance. Therefore, the teacher must consider three important aspects of oral presentation: selecting the overall method of presentation, using the voice to communicate, and using the body to communicate. Meanwhile, in selecting method when presenting the speech, it should be based on at least four criteria: the type of speaking occasion, the seriousness and purpose of the speech, audience analysis, and the students’ strengths and weaknesses as a speaker. Referring to those criteria, the method of presentation should be impromptu, memorized, read from a manuscript, and extemporized (Ehninger, Gronbeck, McKerrow, & Monroe, 1986). Those methods have the same purpose which is used to ease the students in speaking when presenting the speech. However, not all of the methods can be applied. The teacher must consider first the students’ level, purpose of speaking, and learning material, in order to determine the appropriate methods which can benefit the students. Related to the explanation above, the brief definitions of those four methods of presentation are (1)impromptu speaking is delivering a speech without advance preparation. (2)memorized speaking is delivering a speech word for word from memory without using notes. (3) manuscript speaking is reading a speech from prepared text. (4) Extemporaneous speaking is speaking from a written or memorized speech outline without having memorized the exact wording of the speech (Beebe & Beebe, 2009). In this study, the chosen method is impromptu speech. Impromptu speech is delivering a speech without preparing in advance (Beebe & Beebe, 2009). However, Puteh (2006) said that an impromptu speech is a mini speech delivered with a little or no immediate preparation time given to the speaker. Based on the two different definitions of impromptu speech above, the researcher chooses the second definition. The researcher realizes that eleventh graders are still beginners to use this method. So, they need times to focus their ideas. In addition, by using impromptu speech method, the teacher can give a challenging atmosphere in the class, so that the students do not feel demotivated in following the lesson. Moreover, the use of impromptu speech method can help the students to express their opinions or ideas about some issues or topics. In this study, impromptu speech method is implemented in teaching speaking hortatory exposition text. The researcher believes that this method will ease the students in learning speaking hortatory exposition text. Hortatory exposition text is a text which explains to the readers or listeners that something should or should not be in case. In that text, the students must elaborate their evidences about some issues and give a recommendation related to their explanation. This text is appropriate to impromptu speech method because the students can share information based on their experience or their knowledge. Moreover, the students can show their emotion while explaining the topics that they have ever experienced. This method is also appropriate to eleventh graders, because the students in this age have a critical thinking and need opportunities for self-expressions. By doing this study, it is expected that the results can be useful for both teacher and students, especially the eleventh graders. The researcher formulates three research questions, those are: 1. How is the implementation of impromptu speech method in teaching speaking hortatory exposition text to the eleventh grade students of SMAN 1 Krian? 2. How are the students’ responses toward the implementation of impromptu speech method in teaching speaking hortatory exposition text? 3. How are the students’ hortatory exposition speaking performance during the implementation of impromptu speech method in teaching speaking hortatory exposition text? METHOD This study used descriptive qualitative since the researcher wanted to describe all the things happened during the observation. The researcher wanted to know the implementation of the study, students’ responses toward the study, and students’ hortatory exposition speaking performance. In this study, the researcher used non participant observation, because she did not get involved in teaching and learning process. The subjects of this study were the English teacher, who has ever implemented this method before and the students of XI IPA 6. This study was conducted in SMAN 1 Krian, particularly in the class of XI IPA 6. In addition, the researcher used field notes, structured questionnaire, and students’ hortatory exposition speaking performance results as the research instruments. Field notes In this study, the researcher reported the teacher’s and students’ activities during the class in the descriptive part. Meanwhile, the researcher gave her comments about the teacher’s and students’ activities in the reflective part. Field notes may include photographs, audio, and video recordings (Ary, Jacobs, and Soresen, 2010). Structured questionnaire In the structured questionnaire, the researcher gave two choices (Ya or Tidak). There are some points which are asked in questionnaire, they are: students’ opinion about English, students’ opinion about speaking English, students’ opinion about impromptu speech method, and students’ opinion about the implementation of impromptu speech method in teaching speaking hortatory exposition text. Students’ Hortatory Exposition Speaking Performance Results The students’ hortatory exposition speaking performance were analyzed by using scoring matrix into grade A, B, C, D which were adopted from scoring matrix by Brown and Yule (1983). The students get A if they can express their opinion, reason, and give support for their reason. They get B if they can only express opinion and reason. They get C if they give opinion and straight description. The last, they get D if they only keep silent. The researcher collected the data through observation, questionnaire, and students’ hortatory exposition speaking task. The researcher did observation four times in January 13rd, 15th, 20th, and 27th, 2014. Besides, the researcher gave two kinds of speaking task. Firstly, four students were asked to come forward and take the topic. Then, they were given four minutes to prepare it. Next, one by one was called to present it in front of the class. Secondly, the students were called by turns and given the different topics from the previous meetings. If the first students had got the topic and prepared the outline, another student would have been called to take the topic and so forth. Every student got three minutes to prepare themselves. After the presentation, there was a discussion section. Due to speaking performance, there were two assessors in order the teacher did not assess them subjectively. In the last meeting, the researcher gave questionnaire which reflected the students’ feeling from the first until the last meeting. After all the data were collected, then they were analyzed and described qualitatively. There are three kinds of activities in analyzing the data; they are data reduction, data display and also conclusion drawing/verification (Miles and Huberman, 1994 in Koshy, 2005). FINDINGS AND DISCUSSION The implementation of impromptu Speech Method in Teaching Speaking Hortatory exposition Text The observation was conducted for four days on Monday January 13rd, Wednesday January 15th, Monday January 20th, and Monday January 27th 2014. In this research, the researcher was an observer and also teacher’s partner who gives scores to the students’ speaking performance. The researcher gave scores because the other English teachers were having class at that time. Therefore, the researcher became the assessor instead. Besides, the researcher also recorded the students’ speaking. In the first meeting, the teacher reviewed the previous material which was about hortatory exposition text. the teacher wanted to ensure the students’ understanding about that text. Then the teacher introduced the researcher to the students and told that she will do an observation about the implementation of impromptu speech method to teach speaking hortatory exposition text to the eleventh graders. After that, the teacher explained about impromptu speech method and the first speaking task. For the first section of speaking performance, nine students brought the notes to help them speak up. In the second meeting, the teacher continued the previous task and reminded the students for not bringing the notes anymore. In this meeting, the students’ presentation went smoothly and more natural than before. They could show their emotion in front of the class. Meanwhile, in the firts and second meetings there were little discussion between the speaker and audiences. In the third meeting, the teacher gave the second speaking task. Before doing the task, the teacher informed the students that the topics given would be different from the previous meetings. They were also given three minutes to prepare the material. However, the students disagreed that there was discussion section because the time was not enough. In this task, the students were accustomed to speaking spontaneously. In the fourth meeting, the teacher continued the second speaking task. That was the last observation. In the end of the class, the researcher gave questionnaire to the students. After they answered the questionnaire, the researcher said thanks to the teacher and students for permitting and helping the researcher until the end of the observation. Students’ Responses after the Implementation of Impromptu Speech Method to Teach Speaking Hortatory Exposition Text There were 32 responses that fulfilled the questionnaire, because two of them did not attend the class and practice speaking. The Students’ Opinion about English From the first question, thirty two students said that they liked learning English and none of them did not like learning English. For the second question, there were nine students said that English lesson is easy for them. However, twenty three students said that English lesson is difficult to learn. The Students’ Opinion about Speaking English When the students were questioned whether or not they feel happy when they are asked to speak English in the class, there were fifteen students said that they liked it. However, seventeen students said that they did not like it. The fourth question asked whether or not speaking is the skill that they like most in English, seventeen students said that they liked speaking most and fifteen of them said that speaking is not the skill they liked most. When they were asked about an optimal effort that they always did in order they could speak English well, twenty nine students said that they always did an optimal effort to learn speaking. Three students said that they never did an optimal effort to learn speaking. Meanwhile, many kinds of effort that students did in order they could speak English well, those are eight students always enriched vocabulary; one student took English course; twelve students learnt English through song; eight students learnt English by practicing themselves. The sixth question asked whether grammar was the main cause that made students reluctant to speak English, twenty four students said yes, it means that grammar was the main cause to make students reluctant to speak English. Eight students said that grammar was not the main cause. One student said that it was caused by pronoun; two students said that confidence was the main cause; two students said that the difficulty of speaking English was the main cause; two students had difficulty in memorizing vocabulary; and one student said that tenses were the main cause. The Students’ Opinion about Impromptu Speech Method When the students were asked whether they felt challenged or not while speaking by using impromptu speech method, twenty eight students said that they were challenged. Meanwhile, four students said that impromptu speech method did not challenge them. For the eighth question, they were asked whether speaking by using impromptu speech method could make them to be active in the class, twenty nine students said that they became active speaking after using impromptu speech method. However, three students said that they still could not be active in speaking English. The ninth question stated that fifteen students were happy when they were asked to speak English by using impromptu speech method. However, seventeen students said that they were unhappy when they were asked to speak English by using that method. When they were asked whether speaking by using impromptu speech method was more helpful to make them speak fluently than memorized speaking, twenty six students said that it was more helpful than memorized speaking. However, six students said that impromptu speech was not more helpful than memorized speaking. The Students’ Opinion about the Implementation of Impromptu Speech Method in Teaching Speaking Hortatory Exposition Text The eleventh question asked about the students’ feeling while learning hortatory exposition text by using impromptu speech method. Seventeen students said that they felt happy. It could be seen when the students were actively asking the speaker. Not only that, the students also could be more expressive in speaking. Therefore, they felt happy to get impromptu speech method. Meanwhile, fifteen students felt unhappy while learning hortatory exposition text by using impromptu speech method. It was because those students rarely practiced their speaking, so they felt unhappy when the teacher asked them to speak in front of the class. When they were asked whether or not impromptu speech method could make them motivated in learning hortatory exposition text, twenty three students said that they were motivated. Meanwhile, nine students said that they were not motivated in learning hortatory exposition text by using impromptu speech method. The thirteenth question asked whether impromptu speech method could make hortatory exposition text easier and more interesting to learn. Twenty two students agreed with it. However, ten students disagreed that impromptu speech method could make hortatory exposition text easier and more interesting to learn. For the fourteenth question, twenty four students said that impromptu speech method could help them to express themselves and their feeling while learning hortatory exposition text. However, eight students said that they still could not express themselves and their feeling although using impromptu speech method. The last question asked whether or not impromptu speech method is appropriate to learn hortatory exposition text. Eighteen students said that it was appropriate, thirteen students said that it was not appropriate, and one student said that it could be appropriate to learn hortatory exposition text. The Students’ Speaking Hortatory Exposition Performance There were two speaking tasks which were conducted in four meetings. The first task was conducted in the first and the second meeting. Meanwhile, the second task was conducted in the second and the third meeting. The Students’ Speaking Performance of the First Task Based on the analysis of the first task of speaking hortatory exposition text by using impromptu speech method, it could be concluded that there were many students who were not accustomed to speak spontaneously. Nine students still brought notes to help them speak up in the first meeting. However, in the second meeting, most of the students can improve their speaking well. It can be seen the result of their speaking in the example below. Grade A Student #1 All people in the world want to look beautiful or handsome, especially girl. You know, girls in the world want to make their face look beautiful for their boyfriend, friends, or others. But, don’t you know the impact of plastic surgery? First impact is broke your skin face, because many girls through the plastic surgery but not by the good doctor, they want to get cheap price. But they don’t know the impact if they through the plastic surgery but not good doctor. Second impact is when you do plastic surgery you are not like you before. For example, when you in twenty one years old you got married and you have a child but when you twenty five years old do plastic surgery. So, when the child is grow up, their face not like your face. You know, like that. So many people will ask, is it your child? Is it your daughter? Like that. My recommendation, you should thankful to God because, you know your face is beautiful like as you are. Based on the speaking result above, it was categorized into grade A because the speaker could express her opinion, reason, and gave support for her reasons. Although there were some grammatical mistakes in the sentences, the main point is the speaker could speak naturally without bringing notes or even memorizing the text. Grade B Student #2 Students should learn English from early age. In era globalization, English is very important because English international language. So that, we need into communication English for people in the world. Therefore, English should learn from early age. Another, pay attention in subject to learn because many tests that include English for the material. My recommendation is teacher must teach the students to learn English from the early age. The speaking result above was categorized into grade B because the speaker only gave opinion and reason. It could be seen that she could only give opinion about the importance of learning English from early age. It was needed because the students needed to communicate with people in the world. However, she did not give support for her reason, such as the real implementation of using English for students in the future. Moreover, she also did not give example of the test that need English skill. Therefore, her speaking was categorized into grade B. Grade C Student #3 I will present about character building is important for students. As we know, in this era, there are so many students that doesn’t have good morality character. You know that now the religious method for learning seldom use in the school activity. Building character is most very important not use general lesson but we must use the religious lesson like in the Al-Baqarah, we are asked to follow the straight part. The result above was characterized into grade C because the speaker only gave opinion and straight description. It could be seen that the speaker only stated his opinion about the importance of building students’ characters through religious lesson. However, the speaker did not explain the reason that religious lesson is better than general lesson. Moreover, he did not explain about the implementation of it for students in the school. Grade D The student would got grade D, if she/he did not say anything in front of the class or only kept silent. However, none of students who got grade D because all of them delivered their arguments, except two of them who had not presented yet because they were absent at the first and second speaking task. The Students’ Speaking Performance of the Second Task Based on the analysis of the second task of speaking hortatory exposition text by using impromptu speech method, it could be concluded that the students could improve their speaking and express themselves without bringing notes. It can be seen in the example below. Grade A Student #4 We as students must be know that in nowadays there are so many social media. For example facebook, twitter, friendster, line, kakao talk. You must be remember that things in the world have advantage and disadvantage, like social media. You know that social media has so many disadvantages. For example, social media can decrease our actual relationship, like with friends, with out mother, our parent, because if we use social media, we usually focus in our hand phone. So, we will not care about everyone around us. So, that is, social media can decrease our relationship with other people. But you can also remember that social media can give advantage too. Example it happens in my sister, my sister is school in the UNESA college and usually in their school. They use facebook to promote task to students. So, they give task to the students with facebook. That is because facebook is really fast and everyone has it. So, they promote some task information, which will fast deliver to the students. But social media can be happen criminal, example like gambler. If you see on the television you see that some money will lost because of facebook. So, that’s really really bad. My recommendation, we are young generation, we must have good decision. We must manage our time when we are studying or refreshing with facebook. So we must manage our time with good. Based on the speaking result above, the speaker could deliver her opinion, reason and support for reasons clearly and completely. Moreover, her explanation could be easily understood by the other students, because she gave examples based on her own experiences. Therefore, she could deliver the speech smoothly. Due to her wonderful speaking performance, her speaking was categorized into grade A. Grade B Student #5 Smoker in the public transportation is really disturbing. My first argument is many people are not aware of the healthy other. My second argument, passive smoking is more dangerous than active smoker, because they inhale smoke from active smoker directly although they don’t smoke. My recommendation is I think we have to appreciate other people’ health. Based on the speaking result above, it could be categorized into grade B because the speaker could only give opinion and reasons. It could be seen that the speaker said that the passive smokers would get more disadvantages than active smokers, because they inhaled the smoke from active smokers directly. Nevertheless, the speaker did not give examples of public transportation that mostly experience that situation and how to overcome it. Overall, her speaking was good and easy to understand, although there were some grammatical mistakes. Grade C Student #6 I will present about hortatory. The thesis is sport is very important for your body. First argument, you can sport or run, jump, swimming, or etc. My recommendation is you must sport everyday anywhere for your body healthy. For the speaking result above, it could be categorized into grade C because the speaker only gave opinion and straight description. It could be seen that she stated her opinion about sport that could make the students healthy. Then, she explained the various sports that students could do. However, she did not give explanation why sport could make students body healthy. Moreover, she did not explain when the appropriate time to do sport is and how many times the students should do sport in a week. That information was not explained in her speaking. Grade D It was as the same as the speaking result in the first task, none of students got grade D because all of them could deliver their short speech. However, two of them did not get scores in the first and second task, because they were absent. Discussions The discussion explains the result of the implementation of Impromptu Speech method to teach speaking hortatory exposition text, the students’ responses after the implementation of Impromptu Speech method to teach speaking hortatory exposition text, and the result of students’ hortatory exposition speaking performance. The Implementation of Impromptu Speech Method to Teach Speaking Hortatory Exposition Text to the Eleventh Graders at SMAN 1 Krian Based on the result of four meetings on January 13rd, 15th, 20th, and 27th 2014, it could be seen that the implementation of impromptu speech method could make the students improve their oral expression, develop their confidence in public speaking, think quickly and develop their communication skill (Puteh, 2006). The implementation was appropriate with F.Verderber and Verderber (2003) that the students have to determine a goal clearly, adapt material to the audiences, gather information and then organize the material. In the first meeting on January 13rd 2014, the teacher firstly gave task to the students to answer several questions based on the hortatory exposition text. Then she asked the students about the generic structure of hortatory exposition text. After that, the teacher asked the students to find out the generic structure of hortatory exposition text based on the text that they have read. After the students have already understood about hortatory exposition well, the teacher provided several topics based on the students’ interest level (Ikeguchi, 1996). Then she asked the students to make speaking performance by using impromptu speech. Before doing that, the teacher explained to the students about impromptu speech and the steps of doing impromptu speaking, such as determine a goal clearly, adapt material to the audiences, gather information and then organize the material (F.Verderber and Verderber, 2003). Next, the students were asked to make impromptu speech by improving the outline they have made. However, nine students were not ready to speak if they did not bring the outline. Fortunately, most of the students could improve it by themselves (Puteh, 2006). After they presented it, they had to answer one question from another student. There was little discussion for every performance. In the second meeting on January 15th 2014, the teacher firstly reviewed the previous material which was about hortatory exposition text. After the students remembered the generic structured of it, the teacher continued the first task of speaking performance. Before starting the speaking performance, the teacher gave a warning to the students for not bringing the outline while delivering speech. Then the students agreed with it. They were trained to think quickly (Puteh, 2006). As a result, the students performance was getting better than before (Xue-Ping, 1997). Although they could not speak as many as before, the students could express their emotion and do the real speaking. After they presented it, they had to answer the student’s question. Most of them could give a satisfied answer to another student. In the third meeting on 20th January 2014, the teacher firstly explained about the second task of speaking performance. It was still the same as the first task, which was individual performance. Moreover, it still used impromptu speech method. What made it different was the time given, topics, and implementation. In the second task, the teacher did not call four students to come forward and take the topic, but she called the students in turns based on the attendance list. After they took the topic, they were given three minutes for preparing the outline. However, for the second task, there was no discussion section because the time was not enough to have half of the students’ performance in one day. In the third meeting, the students began to be accustomed to speak spontaneously (Ehninger, et.al., 1986). It was shown by their speaking result and expression. In the end of the class, the teacher gave feedback on the students’ speaking performance. In the fourth meeting on January 27th 2014, it was the last observation of speaking hortatory exposition text performance. Then the teacher continued the second task of speaking performance. She called half of students who had not presented yet. They were called by turns based on the attendance list. The students could be more expressive in their second task. After all of the students had presented hortatory exposition text, the teacher gave feedback to them. After implementing impromptu speech method, the students speaking ability was getting better because they could speak naturally with the limited time of preparation. Besides, they could improve oral expressions while delivering the message of their speech and become more confidence in speaking in front of the class (Puteh, 2006). The Students’ Responses Toward the Implementation of Impromptu Speech Method to Teach Speaking Hortatory Exposition Text After the implementation of Impromptu Speech method, the teacher gave a questionnaire which contains fifteen questions. Based on the questionnaire result, it could be concluded that the students were happy while learning English, although English is difficult subject for them to learn. However, many students were reluctant to speak English in front of the class, although they actually liked speaking. It was caused by some factors, such as they had difficulty in grammar, tenses, pronoun, vocabulary, confidence, or even in speaking itself. Therefore, they did an optimal effort in order they could speak English well, for example, they enriched their vocabulary; took English course; learned English through song and movie; and practiced it themselves. When the students were introduced with impromptu speech method, they were challenged to speak English by using that method. Although, half of them do not like to speak English spontaneously, they realized that impromptu speech method could help them to be active in the class. Moreover, they thought that impromptu speech method really helps them to speak English fluently better than memorizing the script. Because the students were learning hortatory exposition text, therefore, that method was used to teach speaking hortatory exposition text. By implementing that method, they were happy to learn speaking hortatory exposition text. Furthermore, they felt motivated to learn hortatory exposition text, if they used that method. They also thought that impromptu speech method make hortatory exposition text easier and more interesting to learn. The most important point is, the impromptu speech method could help the students express their emotion (Puteh, 2006). It is something that they never get, if they only memorize the sricpt. At last, more than half students stated that impromptu speech method was appropriate for learning hortatory exposition text. The Findings of Students’ Hortatory Exposition Speaking Performance In assessing speaking production, the researcher used task type opinion-expressing (Brown and Yule, 1983). In opinion-expressing, there are four types of response: if the students can give opinion, reason, and support for reason, they belong to grade A; if only opinion expressed and reason given, they belong to grade B; opinion expressed or straight description belongs to grade C; and silence belongs to grade D. Here the teacher gave the students two kinds of speaking tasks. The teacher and the researcher gave scores based on the students’ response type toward the topic. Besides, the researcher also recorded the students’ speaking in order the researcher could get valid data. The teacher saw that the students’ speaking performance got a good progress. It could be seen from the students’ speaking hortatory exposition result from the first task and the second task. Before the researcher analyzed it, the students had done the steps in terms of impromptu speaking, such as determining a goal, adapting material to the audience, gathering information, and organizing the material (F.Verderber and Verderber, 2003). In the last meeting, the researcher did not forget to discuss the students’ score with the teacher in order we could get the general scores of students’ speaking performance. The Discussion on the Students’ Speaking Performance in the First Task Based on the students’ hortatory exposition speaking performance result in the first task, it could be seen that many students were not ready to present their speaking by using impromptu speech method. It happened in the first meeting, many of them could not speak up if they did not bring the outline. However, some students could improve it themselves. For the second meeting, all of students could speak spontaneously, although they gave different type response toward their topic. In the first task, there were seven students who got grade A and thirteen students who got grade B. It means that the topics were easy and knowledgeable for students; hence the students could give their arguments. Meanwhile, there were twelve students who got grade C; it means that those students were not accustomed to speaking English spontaneously. Hence, they could not elaborate their arguments and gave support for their reasons. Next, none of the students who got grade D, it means that all of the students actually have a willing to speak English. What makes them different are how much they produce it and how often they practice it. The Discussion on the Students’ Speaking Performance in the Second Task Based on the students’ hortatory exposition speaking performance result in the second task, it could be seen that the students had been accustomed to using impromptu speech method. At the third and fourth meetings, the students could speak English without bringing the outline. Moreover, they could also express their feelings and showed their body gestures such as hands and bodies to communicate. In the second speaking task, there were twelve students who got grade A. It means that the students’ speaking results were satisfying. Although the students were given the different topics, the topics were still interesting for them and knowledgeable (Ikeguchi, 1996). Then, there were fifteen students who got grade B. The numbers of students who got grade B were also satisfying. It means that mostly the students could deliver their opinions and gave their reasons. Next, there were five students who got grade C, it means that the numbers of students who got grade C were decreased. Then none of them who got grade D. Based on the result above, it could be concluded that the students’ hortatory exposition speaking performance from the first task until the second task was satisfying. CONCLUSION AND SUGGESTIONS Conclusion In this study, there are three conclusions that are taken from the result of the study based on the observation in SMAN 1 Krian. Those are: impromptu speech method was successfully used to teach speaking hortatory exposition text to the eleventh graders of SMAN 1 Krian. Next, based on the result of questionnaire, seventeen students felt happy while learning hortatory exposition text by using impromptu speech method. It was because impromptu speech method could engage them in learning speaking hortatory exposition text. Moreover, it could make them express their feeling and become active speaker in the class (Puteh, 2006). The use of Impromptu Speech Method could help the eleventh grade students of SMAN 1 Krian in learning speaking hortatory exposition text. Suggestions Based on the data interpretation and the previous conclusion, the researcher has some suggestions to the teachers and the other researchers. Firstly, In teaching senior high school students, the teacher should know and understand their characteristics because the students in this stage have different characteristics from junior high school students. Secondly, The English teachers must be creative in teaching and learning process especially in teaching speaking, because many students are reluctant in speaking English. At last, the researcher would like to invite the next researchers who want to conduct the similar study in order this study gets improved, such as using the same field but different subjects and material. REFERENCES Ary, D., Jacobs, L. C., & Sorensen, C. (2010). Introduction to Research in education (Eighth edition ed.). Belmont: WADSWORTH CENGAGE Learning. B-Ikeguchi, C. (1996). Training for Impromptu Speaking and Testing Active Listening. The Internet TESL Journal, 2(9). Beebe, S. A., & Beebe, S. J. (2009). Public Speaking AN AUDIENCE-CENTERED APPROACH (Seventh Edition): Pearson Education, Inc. Brown, G., & Yule, G. (1983). Teaching the Spoken Language-An approach based on the analysis of conversational English. New York: Cambridge University Press. Ehninger, D., Gronbeck, B. E., McKerrow, R. E., & Monroe, A. H. (1986). PRINCIPLES AND TYPES OF SPEECH COMMUNICATION (Tenth Edition). F.Verderber, R., & Verderber, K. S. (2003). Effective Speaking (Twelfth ed.). Belmont: Wadsworth. Jianing, X. (2007). Storytelling in the EFL Speaking Classroom. The Internet TESL Journal, 13(11). Pennington, M. (2009). Characteristics of High School Learners. Puteh, F. (2006). Effective Oral Communication UHB 3052. Universiti Teknologi Malaysia. Xue-Ping, G. (1997). A Scheme for the Obtaining of Language Skills. The Internet TESL Journal, 3(6)